The Efforts Of Tourism Awareness Groups (Pokdarwis) In Training Improvement And Utilization Of Local Potential As A Strategy For Ecotourism Development Of 1000 Mangrove Lembungs (Case Study In Ecotourism 1000 Mangrove Lembung) - M. Salim; Mochammad Wispandono (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
This study discusses the problems that exist in Ecotourism 1000 Mangrove Lembung. The problems that are being faced by members of the Green Belt Pokdarwis are the decrease of knowledge, skills, creativity and attitudes in managing and developing Ecotourism 1000 Mangrove Lembung and the decrease in utilizing the potential of mangrove forests because they are still lazy to participate in training. This study aims to describe Pokdarwis efforts in increasing training and utilizing local potential as a development strategy and it can improve the knowledge, skills, and attitudes of Pokdarwis members in Ecotourism 1000 Mangrove Lembung. The approach used in this research is qualitative research with descriptive research type and using case studies. The data collection techniques using interviews, observation, and documentation, and the validity of the data using credibility, transferability, and confirmability tests. The data analysis technique uses data reduction, data presentation, and drawing conclusions as proposed by Miles and Huberman in Hamzah. The conclusions of this study are : 1) After attending training the performance of Pokdarwis members is getting better in utilizing local potential, it can be seen from the awareness of members of the Green Belt Pokdarwis in educating the community about maintaining cleanliness in Ecotourism 1000 Mangrove Lembung, and Green Belt Pokdarwis facilitating UMKM in surrounding community by providing places to introduce their production, namely mangrove coffee, mangrove tea, mangrove syrup and provide supporting facilities for tourists to travel, 2) In the management and development of Ecotourism 1000 Mangrove Lembung the performance of Pokdarwis members is getting better after attending training, in terms of knowledge Pokdarwis members are aware of tourist cleanliness so that the tour looks clean and beautiful, in terms of skills it starts to look good, the arrangement of photo spots, the views and the supporting facilities, as well as the attitude of all members that is already friendly and the service is really serves the visitors who come to this tour.